The Engineering Investigation of the Water Flow past the Butterfly Valve - Chaiworapuek, Weerachai (Trinity College Dublin. School of Engineering. Mechanical & Manufacturing Engineering, 2007)
This paper presents a numerical simulation of flow past the butterfly valve in static and dynamic analysis using commercial fluid dynamics software FLUENT. In static analysis, the positions of the disk were set to be 0 ( completely opened ), 30, 45, 60 and 75 degrees under 1, 2 and 3 m/s water speed. The values of angular velocity were set to be 0.039 and 1.57 rad/s under 1 m/s water speed in dynamic analysis. The study focuses on the investigation of the characteristic of loss coefficient and torque behavior of the 150 mm and 300 mm butterfly valve. From the results obtained, it was found that the loss coefficient and torque values increased when the disk angle was increased. By increasing the water speed, the loss coefficient remained constant while torque value increased. In dynamic analysis of both angular speeds, the maximum torque occurred around 70-80 in closing turn and 100-110 in opening turn. The experiment was also carried out to verify the numerical results. By comparing between the experimental and numerical method, it was found that the loss coefficient and torque value could be determined responsibly. The acceptable comparisons were seen.
Keywords: Butterfly Valve; Loss Coefficient; Torque; Numerical Simulation